Plant-mediated Green Synthesis of Nanoparticles NiCoFe2O4 Photocatalyst Using Africa Leaves Infusion - Siti Rodiah; Catur O. Ditiyaningrum (Universitas Tadulako, 2022)
Nanoparticles (NPs) can be synthesized using a simple and environmentally friendly method by utilizing infuse of the plant. The secondary metabolites contained in infused Africa leaves were used as reducing and stabilizing agents in the synthesis of NiCoFe2O4 NPs. The characteristics and photocatalytic activity of NiCoFe2O4 against the photodegradation of diazinon have been investigated using UV-Vis, FTIR, XRD, and SEM. The UV-Vis spectra showed that NiCoFe2O4 had been formed, as established with a maximum absorbance peak at 277 nm. The FTIR results also confirmed the presence of a ferrite spinel group at a wave number of 565cm-1. The XRD diffractogram showed a cubic crystal of NiCoFe2O4 with a size of 8.79 nm, which was also confirmed from the SEM images that the NPs were slightly agglomerated with an average size of 94.37 nm. The photocatalytic performance of NiCoFe2O4 against diazinon which was carried out for 300 minutes under UV light obtained a degradation percentage of 72.40% producing diazoxide, 2-isopropyl-6-methyl-4-pyramidal (IMP) and diethyl phosphonate. It was concluded that infused African leaves had an active role in the synthesis of NiCoFe2O4.